Association of micronutrient status with thyroid function in adolescent Afghan refugees; a cross-sectional study - Saima Shaheen; Muhammad Shahzad; Nabila Sher; Muhammad Shabbir Khan; Khalid Iqbal; Habab Ali Ahmad; Simon C Andrews (Thyroid Research)
Abstract Micronutrients play a crucial role in several metabolic processes including thyroid hormone metabolism and functions. The current study aimed to assess the associations between thyroid hormone levels and micronutrient status in a cohort of adolescents Afghan refugees residing in a refugee camp in Pakistan. A randomised, community based, cross-sectional study design was employed to recruit 206 adolescent (both male and female) Afghan refugees aged 10–19 years. Sociodemographic data, anthropometric assessments and blood samples were collected using standard methods. Serum vitamins, minerals and thyroid hormones levels were assessed using ELISA, electrochemiluminescence and inductively coupled plasma mass spectrometry (ICP-MS) respectively. Overall results showed the median levels of T3 and TSH were significantly higher (p < 0.05) in younger adolescents (10–14 years) compared to 15–18 year olds while T4 was significantly higher in boys compared to girls. Correlational analysis between serum micronutrients status (vitamin D, vitamin B12, ferritin, folate, zinc, copper, selenium) and thyroid hormones revealed significant relationships in different age groups. Overall, vitamin D exhibited a statistically significant positive correlation with T4 (r = 0.279) in the combined, younger (r = 0.277) and older (r = 0.319) age groups. In contrast, a statistically significant but negative correlation was observed when zinc levels were compared with T3 (r=-0.288) in the older age group and with T4 (r=-0.195) in the younger age group. In conclusion, micronutrients status, especially vitamin D and zinc, have important implications for thyroid health and thereby require close monitoring in any thyroid deficiency related disorders in vulnerable population such as refugees. Clinical trial number: Not applicable.